Two new species of ascaridoid nematodes in Brazilian Crocodylomorpha from the Upper Cretaceous - Cardia, Daniel F.F. [UNESP]; Bertini, Reinaldo J. [UNESP]; Camossi, Lucilene G. [UNESP]; Letizio, Luiz A. [UNESP] (Elsevier, 2019)
Two new ascaridoid species, Bauruascaris cretacicus n. gen. et n. sp., and Bauruascaris adamantinensis n. gen. et n. sp., are described based on the fossils of eggs preserved in 80–70 million year old phosphatized coprolites of Crocodyliformes, chronologically assigned to the Upper Cretaceous (Campanian/Maastrichtian age), collected from sedimentary rocks of the Bauru Group, Adamantina Formation in the municipality of Santo Anastácio, in the southwestern region of the state of São Paulo, Brazil, South America. This paper describes the oldest ascaridoid species ever recorded in Crocodylomorpha. Hence, this article contributes to the body of knowledge about the evolutionary history of this nematode group. It also offers a clue about the composition of the parasite fauna of these reptiles from the Late Cretaceous, which is still unknown despite numerous studies about various aspects of their biology and the pioneering paleoparasitological analysis of animal coprolites by South American researchers.
Keywords: Ascaridoidea; Coprolites; Crocodyliformes; Nematoda; Paleoparasites; Systematics